Cutaneous Hamartoma in a Paediatric Patient: A Case Report on Accessory Eyelashes and Auricular Lesion - Sabah Alotaibi; Mohammed Sawabi; Mutlaq Althobaiti (Metallurgical and Materials Engineering, 2024)
Background: Cutaneous hamartomas are rare, benign congenital malformations involving the abnormal proliferation of native tissue components in an irregular arrangement. They can present in various anatomical regions, often posing diagnostic challenges. Accessory eyelashes and auricular lesions are uncommon manifestations of cutaneous hamartomas, necessitating careful evaluation to differentiate them from other nevoid or choristomatous conditions. Case Presentation: We report the case of a 4-year-old female with no significant medical history, presenting with a pedunculated lesion measuring 0.5 × 0.5 cm on the left outer canthus of the eye, along with a smaller lesion on the right ear. The lesions were asymptomatic, showing no erythema or discharge. The patient underwent surgical excision of both lesions under general anesthesia. The left accessory eyelash lesion was removed using an elliptical incision, while the right auricular lesion was excised and repaired with subcutaneous sutures. Histopathological examination of the left canthal lesion revealed large hair follicles intermixed with sweat glands and fatty tissue in the dermis, confirming the diagnosis of a cutaneous hamartoma. The findings excluded differential diagnoses such as distichiasis or choristoma. Conclusion: This case highlights a rare presentation of cutaneous hamartoma involving accessory eyelashes and an auricular lesion in a pediatric patient. Surgical excision, coupled with histopathological analysis, remains the cornerstone for accurate diagnosis and effective management. Awareness of such atypical presentations is essential for early intervention, ensuring favorable cosmetic and functional outcomes. Further studies are needed to explore the pathogenesis and optimal management strategies for cutaneous hamartomas.